Karakterisasi Smart Flavor Ikan Lele (Clarias sp.) dengan Reaksi Hidrolisis Enzimatis Menggunakan Protease Biduri - Dini Indah Kartikosari (Fakultas Teknologi Pertanian, 2024)
The umami taste in food comes from MSG (Monosodium glutamate) which is a synthetic additive. MSG is safe for consumption if it is in accordance with the recommended dosage but if it exceeds the limit and continues for a long period of time, it can cause various side effects for health. High protein content in fish can be used as a substitute for MSG smart flavor ingredients. Catfish is a type of high protein fish and the price is relatively cheap. One of the protease enzymes that can hydrolyze fish protein is Protease from biduri plant. Differences in the concentration of enzymes used and hydrolysis time can produce different characteristics of smart flavor. This study aims to determine the effect of biduri protease enzyme concentration and hydrolysis time on smart flavor characteristics of catfish and determine the best treatment combination. The experimental design used in this study is a randomized Group Design (RAK) with 2 factors. The first factor is the concentration of the enzyme protease biduri (A) as much as 1, 2 and 3%. The second factor is the hydrolysis time (B) for 2, 4 and 6 hours. Parameters tested in this study include color brightness, yield, water content, dissolved protein content, degree of hydrolysis, antioxidant activity and effectiveness test. The results showed that differences in enzyme concentration (1, 2 and 3%) had a significant effect on color, water content, soluble protein, degree of hydrolysis and antioxidant activity. But hydrolysis time (2, 4 and 6 hours) had a significant effected on color, yield, water content, soluble protein, degree of hydrolysis and antioxidant activity. The increase in enzyme concentration can increase yield value, dissolved protein content, degree of hydrolysis and antioxidant activity. The same is indicated by the increase in the time of its hydrolysis. Smart flavor catfish with the best treatment based on the effectiveness test is found in the sample with the concentration of biduri protease enzyme 3% and hydrolysis time 6 hours with a color brightness value of 90.73%, yield of 78.95%, water content of 8.63%, soluble protein of 1.30 mg/ml, degree of hydrolysis of 58.19% and antioxidant activity of 54.14%.
Reaploud Repository February_Hasyim
Keywords: Smart Flavor; Catfish; Calotropin Enzyme.